2020
DOI: 10.1007/s00107-020-01604-y
|View full text |Cite
|
Sign up to set email alerts
|

Insights into modification of lignocellulosic fillers with isophorone diisocyanate: structure, thermal stability and volatile organic compounds emission assessment

Abstract: This study presents an analysis of the structure and properties of different types of lignocellulosic fillers modified by isophorone diisocyanate (IPDI) to provide insights into the possibility of their application to the manufacturing of wood polymer composites (WPCs). Moreover, it deals with the environmental aspects of modified fillers, by assessment of volatile organic compounds (VOCs) emitted during modification, as well as from final products. Three types of commercially available lignocellulosic fillers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…This chemical is applied industrially as a plant growth regulator by farmers [ 53 ]. Therefore, it was not detected in our previous work related to the cellulose and wood flour obtained mostly from the processing of conifers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This chemical is applied industrially as a plant growth regulator by farmers [ 53 ]. Therefore, it was not detected in our previous work related to the cellulose and wood flour obtained mostly from the processing of conifers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…This chemical is applied industrially as a plant growth regulator by farmers [53]. Therefore, it was not detected in our previous work related to the cellulose and wood flour obtained mostly from the processing of conifers [54]. limonene was classified as 3, which is related to serious temporary or moderate residual injuries caused by short exposure.…”
Section: Volatile Organic Compounds Emissions During Extrusion Of Bsgmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies reported very similar particle size distributions between pine and oak; others reported that hardwood dust is finer than softwood dust [25]. Depending on the treatments to which wood has been subjected before machining, dust can contain preservatives, additives, or adhesives [30][31][32][33][34][35][36][37][38]. The greatest occupational risk is caused by the finest dust particles (inhalable fraction), which, when dispersed in the ambient air, can lead to serious short-term and long-term human health problems [39,40].…”
Section: Introductionmentioning
confidence: 99%